Fine mapping and sequence analysis reveal a promising candidate gene encoding a novel NB-ARC domain derived from wild rice (Oryza officinalis) that confers bacterial blight resistance - Sinha, Pragya; Kumar T., Dilip; Sk, Hajira; Solanki, Manish; Gokulan, C. G.; Das, Ayyappa; Miriyala, Anila; Gonuguntala, Rekha; Elumalai, Punniakoti; M. B. V. N, Kousik; S. K., Masthani; Kumboju, Chaitra; et al. (Frontiers in Plant Science, 2023)
Bacterial blight disease of rice caused by Xanthomonas oryzaepvoryzae(Xoo) is one the most serious constraints in rice production. The most sustainable strategy to combat the disease is the deployment of host plant resistance. Earlier, we identified an introgression line, IR 75084-15-3-B-Bderived from O. officinalis possessing broad-spectrum resistance against Xoo. In order to understand the inheritance of resistance in the O. officinalis accession and identify genomic region(s) associated with resistance, a recombinant inbred line (RIL) mapping population was developed from the cross Samba Mahsuri (susceptible to bacterial blight) x IR 75084-15-3-B-B (resistant to bacterial blight). The F2 population derived from the cross segregated in a phenotypic ratio of 3: 1(resistant: 1 susceptible) implying that resistance in IR 75084-15-3-B-B is controlled by a single dominant gene/QTL. In the F7 generation, a set of 47 Homozygous resistant lines and 47 homozygous susceptible lines were used to study the association between phenotypic data obtained through screening with Xoo and genotypic data obtained through analysis of 7K Rice SNP chip. Through composite interval mapping, a major locus was detected in the midst of two flanking SNP markers, viz., Chr11.27817978 and Chr11.27994133on chromosome 11L with a LOD score of 10.21 and 35.93% of phenotypic variation and the locus has been named as Xa48t. In-silico search in the genomic region in between the two markers flanking Xa48t, identified ten putatively expressed genes located in the region of interest. The quantitative expression and DNA sequence analysis of these genes from contrasting parents identified theOs11g0687900 encoding a NB-ARC domain-containing protein as the most promising gene associated with resistance. Interestingly, a 16-bp insertion was noticed in the UTR region of gene in the resistant parent, IR 75084-15-3-B-B, which was absent in Samba Mahsuri. The association of Os11g0687900 with resistance phenotype was further established by sequence-based DNA marker analysis in RIL population. A co-segregating PCR-based INDEL marker, Marker_Xa48 has been developed for use in the marker-assisted breeding of Xa48t.